The programme of the League of Yugoslav Communists : adopted by the 7. congress of the League of Yugoslav Communists held from 22 tot 26 April, 1958 in Ljubljana. (Beograd : Edition Jugoslavija, 1958)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Communistische Partij; Joegoslavië